Cleaner and effective extraction and separation of iron from vanadium slag by carbothermic reduction-chlorination-molten salt electrolysis. (15th February 2021) - Liu, Shiyuan; He, Xiaobo; Wang, Yadun; Wang, Lijun
Abstract: In this work, a cleaner and effective method for selective extraction of iron from vanadium slag was developed, including carbothermal reduction of iron from vanadium slag, chlorination of reduced slag, and electrolysis of chlorinated slag. In the reduction process of vanadium slag, the influence of temperature and C/slag mass ratio on the reduction percentage of FeO, V2 O3, Cr2 O3, MnO and TiO2 were also investigated by isothermal method. Under the optimal process conditions, the reduction percentage of FeO, V2 O3, Cr2 O3, MnO, and TiO2 in vanadium slag is 38.6% at 1100 °C for 135 min and the metallization ratio of Fe is 85.4%. After carbothermal reduction of vanadium slag, the unreduced iron oxide is chlorinated to obtain FeCl2 and the chlorination rate of unreduced iron oxide is 85.6% at 900 °C for 4 h. In the electrolysis process, the selective electrolysis of iron ions is achieved by controlling the potential of electrolysis to obtain metal Fe (95 wt%) with 0.9 wt% of V and 0.25 wt% of Cr at 1.6 V. This is a new and cleaner method for the selective removal of Fe from vanadium slag. This novel and cleaner process has potential application for processing materials with high Fe content and low content of other valuable elements (Ti, Cr, V, Nb, etc) such as rare earth iron ore, vanadium titanomagnetite ore, and chromite ore. Highlights: A new process to selectively extract Fe from vanadium slag was proposed. The reduction percentage of oxides in vanadium slag was 38.6% at 1100 °C for 135 min. The chlorination rate of iron oxide in reduced slag is 85.6% at 900 °C for 4 h. Metallic iron with 95 wt% Fe, 0.9 wt% V and 0.25 wt% Cr was obtained by electrolysis.